Agricultural fires in the southeastern U.S. during SEAC4RS: Emissions of trace gases and particles and evolution of ozone, reactive nitrogen, and organic aerosol. Issue 12 (22nd June 2016) - Liu, Xiaoxi; Zhang, Y.; Huey, L. G.; Yokelson, R. J.; Wang, Y.; Jimenez, J. L.; Campuzano‐Jost, P.; Beyersdorf, A. J.; Blake, D. R.; Choi, Y.; St. Clair, J. M.; Crounse, J. D.; et al.
Abstract: Emissions from 15 agricultural fires in the southeastern U.S. were measured from the NASA DC‐8 research aircraft during the summer 2013 Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS) campaign. This study reports a detailed set of emission factors (EFs) for 25 trace gases and 6 fine particle species. The chemical evolution of the primary emissions in seven plumes was examined in detail for ~1.2 h. A Lagrangian plume cross‐section model was used to simulate the evolution of ozone (O3 ), reactive nitrogen species, and organic aerosol (OA). Observed EFs are generally consistent with previous measurements of crop residue burning, but the fires studied here emitted high amounts of SO2 and fine particles, especially primary OA and chloride. Filter‐based measurements of aerosol light absorption implied that brown carbon (BrC) was ubiquitous in the plumes. In aged plumes, rapid production of O3, peroxyacetyl nitrate (PAN), and nitrate was observed with ΔO3 /ΔCO, ΔPAN/ΔNO y, and Δnitrate/ΔNO y reaching ~0.1, ~0.3, and ~0.3. For five selected cases, the model reasonably simulated O3 formation but underestimated PAN formation. No significant evolution of OA mass or BrC absorption was observed. However, a consistent increase in oxygen‐to‐carbon (O/C) ratios of OA indicated that OA oxidation in the agricultural fire plumes was much faster than in urban and forest fire plumes. Finally, total annual SO2, NO x, and CO emissions from agricultural fires in Arkansas, Louisiana, Mississippi, and Missouri were estimated (within a factor of ~2) to be equivalent to ~2% SO2 from coal combustion and ~1% NO x and ~9% CO from mobile sources. Key Points: Emission factors measured for 15 agricultural fires in the southeastern U.S. Ozone, PAN, and nitrate formed in aged plumes, and O/C of OA increased Chemical evolution simulated by a Lagrangian plume cross‐section model